2013
DOI: 10.1016/j.cld.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Drug-induced Liver Injury

Abstract: Synopsis Drug induced liver injury (DILI) represents a broad spectrum of liver manifestations. However, the most common manifestation is hepatocyte death following drug intake. DILI can be predictable and dose dependent with notable example of acetaminophen toxicity. Idiosyncratic DILI occurs in an unpredictable fashion at low frequencies implying that environmental and genetic factors alter the susceptibility of individuals to the insult (drugs). An biochemical stress is usually initiated by drugs and their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
185
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(195 citation statements)
references
References 62 publications
0
185
0
10
Order By: Relevance
“…In the latter case, albumin-bound toxins might persist longer in the circulation, or albumin binding might decrease toxicity by decreasing free toxin levels. Indeed, one of the most commonly used analgesics, acetaminophen (para-acetylaminophenol, APAP), is known to bind albumin in the circulation (32) and is toxic to the liver at high doses (33,34). When ingested in excess (above 10 g/d or 200 mg/kg for humans), the hepatocyte glucuronide pathway is saturated, resulting in the production and accumulation of a toxic byproduct, N-acetyl-p-benzo-quinoneimine (NAPQI) (35).…”
Section: Hepatic Fcrn Renders the Liver Susceptible To The Effects Of Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, albumin-bound toxins might persist longer in the circulation, or albumin binding might decrease toxicity by decreasing free toxin levels. Indeed, one of the most commonly used analgesics, acetaminophen (para-acetylaminophenol, APAP), is known to bind albumin in the circulation (32) and is toxic to the liver at high doses (33,34). When ingested in excess (above 10 g/d or 200 mg/kg for humans), the hepatocyte glucuronide pathway is saturated, resulting in the production and accumulation of a toxic byproduct, N-acetyl-p-benzo-quinoneimine (NAPQI) (35).…”
Section: Hepatic Fcrn Renders the Liver Susceptible To The Effects Of Anmentioning
confidence: 99%
“…When ingested in excess (above 10 g/d or 200 mg/kg for humans), the hepatocyte glucuronide pathway is saturated, resulting in the production and accumulation of a toxic byproduct, N-acetyl-p-benzo-quinoneimine (NAPQI) (35). NAPQI depletes glutathione (GSH) and binds in particular to mitochondrial proteins, mainly to the amino acid cysteine, causing oxidative stress, mitochondrial damage, and ultimately hepatocyte death (34,36). We therefore hypothesized that FcRn affects the sensitivity of the liver to toxins, using APAP as a model of liver toxicity.…”
Section: Hepatic Fcrn Renders the Liver Susceptible To The Effects Of Anmentioning
confidence: 99%
“…The risk factors associated with DILI include age (<18 or >65years), obesity, pregnancy, concomitant alcohol consumption, and certain genetic polymorphisms (such as cytochrome P450 polymorphisms). It has been suggested that susceptible populations should not be subjective to re-challenge with drugs suspected of causing DILI [49,[50][51][52][53]. These injuries resemble almost all known liver diseases and there are no pathognomonic findings, even upon liver biopsy, that clarify the diagnosis of DILI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when the clinician suspects of DILI, it is essential to gather additional clinical and laboratory information necessary for differential diagnosis of the cause. The most important key point is to exclude other causes of liver disease (existence of acute/chronic hepatitis, nonalcoholic steatohepatitis [NASH], biliary tract diseases (stones, sand), obesity/metabolic syndrome, circulatory problems, congestive heart failure, concomitant exposure to other hepatotoxic drugs, alcohol or hepatotoxins) [51][52][53]. Some of the drugs that induce DILI and the mechanisms underlying their toxicity are summarized in Table 1 [54-78].…”
Section: Discussionmentioning
confidence: 99%
“…At higher doses, however, NAPQI causes potentially life-threatening liver damage [65]. Acetaminophen toxicity is a leading cause of poisoning and liver damage in the U.S. [66] Albeit rare, idiosyncratic drug-induced liver injury can occur unpredictably even in therapeutic dose ranges, implying that environmental and/or genetic factors may influence individual susceptibilities [67]. In the U.S., the Food and Drug Administration (FDA) has required new warning labels on acetaminophen products to alert consumers about the risks of acetaminophen [68].…”
Section: Common Ed Analgesicsmentioning
confidence: 99%